Validation of a methodology for rearing Spalangia cameroni (Hymenoptera: Pteromalidae) on Ceratitis capitata (Diptera: Tephritidae). Issue 6 (24th April 2014) - Tormos, J.; Sabater-Muñoz, B.; Asís, J.D.; Beitia, F.
Abstract Spalangia cameroni Perkins (Hymenoptera: Pteromalidae) is a pupal parasitoid of the Medfly, Ceratitis capitata (Wiedmann) (Diptera: Tephritidae), one of the principal pests of Spanish agriculture. Spalangia cameroni is a potential biocontrol agent for this pest if methods can be developed to mass-rear it effectively on C. capitata. Here, we report on the use of freeze-killed pupae of C. capitata to maintain a laboratory colony of S. cameroni, with a view to setting up a mass-rearing protocol. Realised fecundity, adult progeny, sex ratio, and superparasitism level were the principal parameters analysed. No significant differences were found in respect of these parameters between living or freeze-killed Medfly pupae used as hosts, although sex ratios showed a bias towards females in the case of freeze-killed pupae. Freeze-killed pupae were concluded to present the best option for the laboratory-rearing of S. cameroni, on account of ease of rearing, and avoidance of the emergence of Medfly adults.